Immigration concerns and social program avoidance: The roles of legal status and family composition among asian and latino communities - Alein Y. Haro-Ramos; Gabriel Sanchez; Matt Barreto (Journal of Migration and Health, 2024)
Objectives: Immigration policies significantly affect immigrants and their families' access to social programs. This study examines the role of legal status and familial composition in Asian and Latino adults’ avoidance of social programs and assesses differences between the groups. We categorized respondents’ familial composition based on whether all household members had the same citizenship status. We created two groups: respondents with cross-status ties and those without. Methods: We use data from 1000 U.S. adults with proximal or distant ties to noncitizens (collected in September 2021) to employ multivariable generalized linear models with binomial family and logit link to assess avoidance of needed social programs due to immigration concerns. Results: Our fully adjusted model reveals that compared to U.S. citizens without familial cross-status ties (i.e., all-citizen household members), legally precarious immigrants (LPI) without cross-status ties (odds ratio (OR)= 3.64, 95 % CI: 1.67–7.96), LPI with cross-status ties (OR=1.71, 95 % CI: 1.14–2.57), and U.S. citizens with cross-status ties (OR=1.66, 95 % CI: 1.14–2.40), were more likely to report avoidance of needed social support programs. Further, an interaction analysis shows that Asian lawful permanent residents with cross-status ties exhibit a higher likelihood of avoiding social programs due to immigration concerns compared to their Latino counterparts. Conclusion: The far-reaching consequences of anti-immigrant policies on noncitizen individuals and their families, including U.S. citizens, may lead to disparities in access to social assistance programs that may exacerbate health disparities. Further, our findings suggest that immigrants’ cross-status ties to U.S. citizen family members may be protective against the harmful effects of anti-immigrant policies.